Factor Analysis Of The Market Environment For Artisanal Dimension Stone In Nairobi, Kenya - K'Akumu, O.A.; Jones, Brian; Yang, Junli (Penerbit Universiti Sains Malaysia, 2013)
Artisanal dimension stone (i.e., blocks cut and shaped from natural rock using hand tools) has attracted scholarly attention as part of the informal sector of the construction industry and as part of the productive enterprise of artisans. One of the areas that intrigue scholars in this respect is the market environment of the subject product. In Nairobi, for instance, researchers have adopted a qualitative approach to the study of the market environment of artisanal dimension stone. We build on the outcomes of previous studies to present a quantitative approach to the factors influencing the market environment of artisanal dimension stone in Kenya by developing the factors identified in the past studies into 24 measurable variables that are then subjected to factor analysis to identify and gauge the principal components. The analysis identifies five principal components that influence the market environment: a difficult marketing terrain, a general lack of specification by building professionals and formal developers, occasional specification by building professionals, a cumbersome stone procurement system, and advantages provided by the use of artisanal dimension stone in building. These include both negative and positive factors, although the negative forces tend to dominate, resulting in an inhibitive rather than a facilitative environment. Recommendations are made to address this situation, including recommendations for an association with a mining advocacy organisation such as Communities and Small-Scale Mining (CASM) or similar institution and the formation of a marketing cooperative by the producing units to help in the formalisation of their transactions.